Mobile learning and games in special education - Standen, Penny; Brown, David (SAGE, 2014)
Information technology is now a ubiquitous presence in all educational settings as well as places in which people work. While most mainstream schools now rely heavily on this technology to support learning, special education was often at the forefront of its adoption even acting as exemplars for mainstream education (Lilley, 2004). Educational virtual environments had been developed in special schools and adult training centres when virtual reality was still a novel technology in education (Standen & Brown, 2004; 2005; 2006). Now no school or educational setting would be imagined without information technology and there have been some exciting developments since those early pioneering days. In this chapter we intend to cover three of those which we think are particularly pertinent for learners with special needs: serious games, mobile computing and the role of users in the development of the technology.